Identifikasi Profil Kesulitan Belajar Fisika Topik Fluida Statis pada Siswa SMA di Kabupaten Demak - Adi, Alik Sus; Sugiyanto, Sugiyanto; Rusilowati, Ani (UPEJ Unnes Physics Education Journal, 2018)
The purpose of this study was to identify students' learning difficulty profile on the topic of static fluid. The study was conducted in three high schools in Demak. Student learning difficulties profiles were measured using a diagnostic test instrument in the form of multiple open-ended options totaling 13 items. To strengthen the data is done interview with some students. Learning difficulties profiles are diagnosed with five approaches, namely learning objectives, material profiles, prerequisite knowledge, misconceptions, and structured knowledge. The results showed that the percentage of learning objectives for each indicator understood the concept of hydrostatic pressure, comparing the hydrostatic pressure on different liquids, understanding Pascal's legal concepts, understanding the concept of the law of Archimedes in floating, floating, and drowning phenomena, and explaining the buoyant force in a row 58.33%; 75.96%; 57.21%; 81.25%; and 98.56%. Percentage of hydrostatic pressure material profile, Pascal law and Archimedes law were 68.40%; 57.21%; and 89.90%. For prerequisite knowledge with 12% percentage, the percentage of material misconception of hydrostatic pressure and Pascal law are 48.08% and 48.08% respectively and knowledge is structured with 4.07% percentage.